1966
DOI: 10.1002/1097-0142(196602)19:2<257::aid-cncr2820190218>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Hamartomatous inverted polyps of the rectum

Abstract: Hamartomatous inverted polyps of the rectum are benign single slightly polypoid intramural masses of the bowel wall formed by an inverted or downward growth of mucosal glands through the muscularis mucosa into the submucosa. The atypical and distorted mucous glands and the ectopic position of both mucous glands and lakes of mucus in these benign lesions may cause an erroneous diagnosis of well‐differentiated carcinoma. Three cases with a differential diagnosis are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0
1

Year Published

1969
1969
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(22 citation statements)
references
References 3 publications
0
21
0
1
Order By: Relevance
“…6 Microscopically, ectopic distorted, slightly atypical mucous glands are present in a more or less circumscribed group in the submucosa, pushing the mucosa up to form a polypoid mass. Hamartomatous inverted polyps may simulate this microscopically, but are different from this present case in terms of their gross configuration and location.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Microscopically, ectopic distorted, slightly atypical mucous glands are present in a more or less circumscribed group in the submucosa, pushing the mucosa up to form a polypoid mass. Hamartomatous inverted polyps may simulate this microscopically, but are different from this present case in terms of their gross configuration and location.…”
Section: Discussionmentioning
confidence: 99%
“…5 This growth pattern may simulate a submucosal invading cancer. "Hamartomatous inverted polyps" also were reported as nonneoplastic lesion 6 ; these are protruded lesionsoccurring in the rectum-and formed by an inverted or downward growth of mucosal glands through the muscularis mucosa into the submucosa.…”
mentioning
confidence: 99%
“…According to Haskell and Rovner (1965) the condition was first described by Cruveilhier (1829-42). Allen (1966), Epstein, Ascari, Ablow, Seaman, and Lattes (1966), and Wayte and Helwig (1967) have described what appears to be a similar or related pathology under the title 'Hamartomatous inverted polyps of the rectum' and 'Colitis cystica profunda'. The expression 'solitary ulcer' has been used at St Mark's Hospital since before World War II (Lloyd-Davies, 1969).…”
mentioning
confidence: 99%
“…Allen [6] in 1966 favored a h a m a r t o m atous pathogenesis. He described 3 patients with rectal lesions and concluded that the a n a t o m y of the lesions and its occurrence in y o u n g adults suggest that it is developmental in origin.…”
Section: Differential Diagnosismentioning
confidence: 99%